The distribution of AB0 and Rh blood groups in the Tabuk region and Medina Munewera, Saudi Arabia - Özsoylu, Şinasi; Alhejaily, Mohammed (The Turkish Journal of Pediatrics, 1987)
The high frequency of group 0 blood seen in the population in Tabuk (53%) and Medina Munewera (44%) is demonstrated. Rh negativity was found to be rare in these areas, 8% and 11%, respectively.